2011
DOI: 10.1017/s0025315411001500
|View full text |Cite
|
Sign up to set email alerts
|

Coral farming: effects of light, water motion and artificial foods

Abstract: Improved coral cultivation will facilitate the reduction of wild harvesting, reef restoration, preservation of biodiversity, and the use of corals as model experimental organisms. In this study, we examine species-specific responses in growth and survival of corals from the effects of light, water motion and artificial (i.e. non-living aquarium trade) food supplements. Three species representing distinct, diverse and abundant coral genera were chosen (Montipora capitata(Mc), Porites compressa (Pc) and Pocillop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…However, feeding frequency may alter this balance, particularly if the nutrient load in the surrounding water decreases water quality and interferes with the natural inorganic nutrient concentrations. Forsman et al (2011), for example, observed a significantly slower growth of M. capitata and P. damicornis, when feeding doses increased too much and deteriorated water quality.…”
Section: Organic Nutrientsmentioning
confidence: 99%
“…However, feeding frequency may alter this balance, particularly if the nutrient load in the surrounding water decreases water quality and interferes with the natural inorganic nutrient concentrations. Forsman et al (2011), for example, observed a significantly slower growth of M. capitata and P. damicornis, when feeding doses increased too much and deteriorated water quality.…”
Section: Organic Nutrientsmentioning
confidence: 99%
“…Practically, in modern aquaria, the efficiency of specific feeds use is often reduced by the presence of several species of fish and invertebrates kept at the same time (Velasco‐Santamaría & Corredor‐Santamaría ; Forsman et al . ). Ornamental fish feed companies try to by‐pass this obstacle by producing feeds with different buoyancy that can be virtually consumed in water surface (flakes), in the middle water layers (soft granulate, food sticks) and on the bottom (tablet and chips).…”
Section: The Home Aquarium Feeds: a Single Feed For 20 Species?mentioning
confidence: 97%
“…It seems that this sector is dominated by aquafeed companies information more than by scientific information (Forsman et al . ). Reproduction also occurs in aquaria and fry nutritional needs are different from adults.…”
Section: The Role Of Scientific Research In Ornamental Animal Feedingmentioning
confidence: 97%
See 2 more Smart Citations